2010
DOI: 10.1021/jp911880u
|View full text |Cite
|
Sign up to set email alerts
|

Full-Dimensional Quantum Reaction Rate Calculations for H + CH4 → H2 + CH3 on a Recent Potential Energy Surface

Abstract: The thermal rate constant of the H + CH(4) → H(2) + CH(3) reaction on the recent potential energy surface (PES) of Corchado et al (CBE) (Corchado, J. C.; Bravo, J. L.; Espinosa-Garcia, J. J. Chem. Phys. 2009, 130, 184314) is computed employing the state-averaged multiconfigurational time-dependent Hartree approach in the temperature range 250-500 K. The CBE PES is global and is based on an analytic functional form that is fast to evaluate. This surface is therefore potentially useful for testing new quantum dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 39 publications
(81 reference statements)
2
33
0
Order By: Relevance
“…Accurate full-dimensional quantum dynamics calculations for six atom reactions have up to now only been presented for cumulative reaction probabilities and thermal rate constants [14][15][16][17][18][19][20][21][22][23] or initial state-selected reaction probabilities 24,25 and studied the H + CH 4 → H 2 + CH 3 , [14][15][16][17][18][19][22][23][24][25] [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] and propagated wave packets representing vibrational states of the activated complex which have been a) Electronic mail: rwelsch@uni-bielefeld.de. b) Electronic mail: uwe.manthe@uni-bielefeld.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate full-dimensional quantum dynamics calculations for six atom reactions have up to now only been presented for cumulative reaction probabilities and thermal rate constants [14][15][16][17][18][19][20][21][22][23] or initial state-selected reaction probabilities 24,25 and studied the H + CH 4 → H 2 + CH 3 , [14][15][16][17][18][19][22][23][24][25] [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] and propagated wave packets representing vibrational states of the activated complex which have been a) Electronic mail: rwelsch@uni-bielefeld.de. b) Electronic mail: uwe.manthe@uni-bielefeld.…”
Section: Introductionmentioning
confidence: 99%
“…17 This PES was chosen because of its numerical efficiency and the existence of tunneling corrected TST 18 as well as MCTDH calculations, 34 which indicated a good agreement with experiment. RPMD calculations have also been reported for the H + CH 4 reaction on this PES, but only at 300 K. 56 Comparison with the converged Shepard interpolated PES developed by Wu et al 16 indicated that this PES is very accurate for the H + CH 4 rate coefficients.…”
Section: Computational Detailsmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21] However, a full-dimensional quantum mechanical treatment of the reaction dynamics is still very difficult. With the exception of the multidimensional time-dependent Hartree [22][23] (MCTDH) calculations, [24][25][26][27][28][29][30][31][32][33][34][35] most quantum dynamical studies of this reaction have been cast in reduced-dimensional models, [36][37][38][39][40][41][42][43][44][45] due to the exponential scaling laws of CPU and memory requirements. Even in the MCTDH work, the J-shifting approximation 46 had to be used in order to make the calculations feasible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside the investigation of gas phase systems (here further calculations ranging from triatomic [76,77] to hexatomic reactions [78][79][80] could be mentioned) also rates for process on surfaces [81,82] and reactions in condensed phase [83,84] studied based on the quantum transition state concept. The dissociative adsorption of N 2 on a stepped Ru-surface was studied by 6D quantum dynamics calculations for a rigid Ru-surface [82] and the effect of surface motion on in the system was considered on TST level [85].…”
Section: From Triatomics To Polyatomic Reactionsmentioning
confidence: 99%